Penyajian Laporan Keuangan Berdasarkan SAK EMKM pada UMKM Rumah Makan di Sosok Kecamatan Tayan Hulu Kabupaten Sanggau - Septania Septania; Sartono Sartono; Wilda Sari (Program Studi Akuntansi Universitas Panca Bhakti, 2026)
This study aims to examine the presentation of financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in a small restaurant business located in Sosok, Tayan Hulu District, Sanggau Regency. This research employs a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation obtained directly from the business owner. The data used in this study consist of raw financial records of the restaurant, which were processed using Microsoft Excel. The data analysis follows the SAK EMKM framework through accounting procedures, including the preparation of general journals, ledgers, adjusting entries, adjusted income statements, and adjusted trial balances. The findings reveal that Bu’De Ketut Restaurant had not previously prepared financial statements in accordance with applicable accounting standards. The owner only maintained simple records of cash inflows and outflows. After applying SAK EMKM, the financial statements produced include a statement of financial position, an income statement, and notes to the financial statements. The analysis of the statement of financial position indicates a stable financial condition at the end of 2023, with the ability to maintain profitability and high operational efficiency. The income statement reflects strong financial performance, generating a significant net income before tax. Furthermore, the notes to the financial statements demonstrate adequate liquidity to support future operations. This study also identifies several obstacles in preparing financial statements, including the nature of the business as a self-managed family enterprise and the continued use of simple accounting practices